"Most Dangerous Pollutant on the Planet”– Plastic Pollution in Bangladesh: Causes, Effects & Solutions - Ahmed, M Jamaluddin (Feni University Journal, 2026)
A synthetic material made from a wide range of organic polymers, such as polyethylene, PVC, nylon, etc., that can be molded into shape while soft, and then set into a rigid or slightly elastic form. Plastic pollution is the accumulation of plastic objects (e.g., plastic bags, plastic bottles, etc.) in the Earth’s environment that adversely affects wildlife, marine life, and humans. Recycling is the best way to reduce plastic pollution: “Make sure that you are recycling the correct way and not adding to the plastic pollution in the environment”. One of the Bangladeshi Chemists has invented a new technique to produce petroleum oil and gas from plastic waste. 1 ton of plastic waste = 13 barrels of petroleum oil. Another best way for recycling plastic wastes (e.g., bags, bottles, etc.) is by using the Blest Machine, which produces 16 barrels of petroleum oil from 1 ton of plastic waste. Plastic bags less than 20 microns are dangerous for the environment because it is totally non-degradable and nonreusable. Another way to reduce plastic pollution is to use jute bags instead of plastic bags, which are highly degradable in the environment. Thick plastic bags (>20 micron), which are reusable, should be used. ‘Papcoat’ is a surface treatment technology for paper. Through a cellulose molecular coating, Papcoat™ provides a 100% paper solution to fully replace plastic films cost-effectively: fully biodegradable, fully compostable, and fully recyclable like any normal virgin paper. Ecobin is cheaper system which contributes to installing a sustainable way of sorting in waste management in developing countries. The Ecobin is a merging of artisanal knowledge and modern technology to build a contemporary solution to beat plastic pollution in Africa. ‘Stopping Toxic Plastic Waste Trade and its Trans boundary Movements’ FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (09-24)